Game logic : level up and create your own games with science activities for kids - Smibert, Angie ("Build it yourself" series., 2019)
Introduces middle-school-age kids to the history and development of games as well as how to create their games through hands-on STEM activities. Includes a timeline, QR codes, discussion questions, sidebars, fact boxes, activities, color photographs and illustrations, a glossary, and resources for further topic exploration.